Analysis of Leadership, HR Practices, Organizational Agility, and Employee Performance at the Emergency Department of XYZ Hospital - Taufik Supriyana Trisaputra; Bernarto, Innocentius (Jurnal Manajemen, 2024)
The Emergency Department (ED) is a complex unit with a dynamic environment characterized by rapid changes, high uncertainty, and many unforeseen possibilities. Therefore, hospitals need to implement appropriate Leadership and HR Practices to achieve Organizational Agility in the ED and improve employee performance to provide the best service to patients. This study aims to analyze Leadership, HR Practices, Organizational Agility, and Employee Performance in the ED unit of Seto Hasbadi Bekasi Hospital. The sampling technique used was a census with a sample size of 65 healthcare workers. The data analysis technique used in this study was Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that Leadership had a significant positive effect on HR Practices, but did not affect Organizational Agility and Employee Performance. HR Practices had a significant positive effect on Organizational Agility. HR Practices also had a significant positive effect on Employee Performance. Furthermore, Organizational Agility had a significant positive effect on Employee Performance. The management of Seto Hasbadi Bekasi Hospital has implemented good HR Practices, which has had a positive impact on the performance of healthcare workers in the ED. The maximum implementation of HR Practices will make the hospital agile, effective, and efficient in handling all conditions in the ED.